2017
DOI: 10.1080/13696998.2017.1331912
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of rivaroxaban for treatment and secondary prevention of venous thromboembolism in the Netherlands

Abstract: Rivaroxaban treatment of patients with venous thromboembolism results in health gains and cost savings compared to LMWH/VKA therapy. This conclusion holds for the Dutch setting, both for the societal perspective, as well as the healthcare perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…There are numerous published studies comparing the cost-effectiveness of rivaroxaban or apixaban with the standard VTE treatment of LMWH and VKA. These consistently show that rivaroxaban and apixaban are cost-effective treatments for VTE compared with standard LMWH/VKA therapy [67][68][69][70][71][72][73] . However, only one study was found that compared the cost-effectiveness of different DOACs 74 .…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous published studies comparing the cost-effectiveness of rivaroxaban or apixaban with the standard VTE treatment of LMWH and VKA. These consistently show that rivaroxaban and apixaban are cost-effective treatments for VTE compared with standard LMWH/VKA therapy [67][68][69][70][71][72][73] . However, only one study was found that compared the cost-effectiveness of different DOACs 74 .…”
Section: Discussionmentioning
confidence: 99%
“…See Data S1 for the search string and the results of the systematic review of the literature. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 …”
Section: Methodsmentioning
confidence: 99%
“…35 In our model, we assumed that all clinically relevant postdischarge VTE would require an inpatient readmission. 36 We acknowledged that not all VTE in practice are treated with an inpatient stay, but that such a conservative assumption favored the model preferring the routine ePpx strategy that we were testing.…”
Section: Costsmentioning
confidence: 99%